Luminescent Behavior of the K2SiF6:Mn4+ Red Phosphor at High Fluxes and at the Microscopic Level. (22nd August 2015) - Sijbom, Heleen F.; Joos, Jonas J.; Martin, Lisa I. D. J.; Van den Eeckhout, Koen; Poelman, Dirk; Smet, Philippe F.
Abstract : Phosphor-converted white light-emitting diodes (LEDs) are becoming increasingly popular for general lighting. The non-rare-earth phosphor K2 SiF6 :Mn 4+, showing promising saturated red d-d-line emission, was investigated. To evaluate the application potential of this phosphor, the luminescence behavior was studied at high excitation intensities and on the microscopic level. The emission shows a sublinear behavior at excitation powers exceeding 40 W/cm², caused by ground-state depletion due to the ms range luminescence lifetime. The thermal properties of the luminescence in K2 SiF6 :Mn 4+ were investigated up to 450 K, with thermal quenching only setting in above 400 K. The luminescence lifetime decreases with increasing temperature, even before thermal quenching sets in, which is favorable to counteract the sublinear response at high excitation intensity. A second, faster, decay component emerges above 295 K, which, according to crystal field calculations, is related to a fraction of the Mn 4+ ions incorporated on tetragonally deformed lattice sites. A combined investigation of structural and luminescence properties in a scanning electron microscope using energy-dispersive X-ray spectroscopy and cathodoluminescence mappings showed both phosphor degradation at high fluxes and a preferential location of the light outcoupling at irregularities in the crystal facets. The use of K2 SiF6 :Mn 4+ in a remote phosphor configuration is discussed.